2003
DOI: 10.1023/a:1022589501039
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Women are not necessarily at greater risk of physical abuse when they are pregnant than before pregnancy. Both the preconception period and the period during pregnancy are periods of risk, which suggests that prevention activities are appropriate during routine health care visits before pregnancy as well as during family planning and prenatal care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
61
1
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(70 citation statements)
references
References 15 publications
6
61
1
2
Order By: Relevance
“…When we compare the results of ‘Are you afraid of your partner or anyone you listed above?’ (1.2%, n = 22) with the results of a set of specific behavioural questions assessing IPV in the 12 months before and/or during pregnancy (20.4%, n = 347), it is clear that measuring violence by means of one general question detects much less violence. This finding has been confirmed by several other authors [12, 15, 18, 22, 23, 45]. An exploratory analysis of the 22 women that declared themselves to be afraid, revealed that these women had a lower socio-economic status, more psycho-social problems and higher violence prevalence rates.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…When we compare the results of ‘Are you afraid of your partner or anyone you listed above?’ (1.2%, n = 22) with the results of a set of specific behavioural questions assessing IPV in the 12 months before and/or during pregnancy (20.4%, n = 347), it is clear that measuring violence by means of one general question detects much less violence. This finding has been confirmed by several other authors [12, 15, 18, 22, 23, 45]. An exploratory analysis of the 22 women that declared themselves to be afraid, revealed that these women had a lower socio-economic status, more psycho-social problems and higher violence prevalence rates.…”
Section: Discussionsupporting
confidence: 74%
“…We were not able to detect any evolution in sexual partner violence and this is probably linked to the small sample size. Similarly, other researchers have demonstrated that prevalence of violence during pregnancy is consistently lower than violence occurring before pregnancy, both in developed [14, 15, 3750] and less developed nations [5156]. Furthermore, we found that 6.3% of the total IPV occurred only during pregnancy (and not in the 12 months before), 28.1% of the women indicated that they only experienced IPV in the 12 months before (and not during) pregnancy.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Using data from the 1996–1998 CDC PRAMS, Saltzman et al . calculated the levels and patterns of physical abuse before and during pregnancy; the prevalence of intimate partner violence across the 16 states was found to be 7.2% (95% CI, 6.9–7.6) during the 12 months before pregnancy, 5.3% (95% CI, 5.0–5.6) during pregnancy, and 8.7% (95% CI, 8.3–9.1) around the time of pregnancy (before or during pregnancy) (47). In a British Longitudinal Study of 7,591 pregnant women, prevalence rates of intimate partner violence were examined during pregnancy and after delivery; compared to the post-partum period, the risk of intimate partner violence was consistently lower during pregnancy (68).…”
Section: Discussionmentioning
confidence: 99%